Challenges facing providers of imported malaria-related healthcare services for Africans visiting friends and relatives (VFRs) - Neave, P; Jones, C; Behrens, R (BioMed Central, 2014)
BACKGROUND: In many non-malarious countries, imported malaria disproportionately affects Africans visiting friends and relatives (VFRs). Most previous research has focused on understanding the knowledge, attitudes and practices of these travellers, but has not examined the quality of prevention, diagnosis and treatment services provided. The aim of this study was to understand the perspective of providers of malaria-related healthcare services to VFRs about factors impacting on the quality of these and to make recommendations about improvements. METHODS: Thirty semi-structured interviews were conducted with practice nurses providing pre-travel health advice (n = 10), general practitioners (GPs) (n = 10), hospital consultants (n = 3), and community pharmacists (n = 7) working in areas of London with large African communities and a relatively high burden of imported malaria. A thematic analysis of the results was undertaken. RESULTS: Time constraints in GPs' surgeries and competing priorities, lack of confidence in issuing advice on mosquito avoidance, the cost of chemoprophylaxis and travel at short notice prevented the provision of adequate malaria prevention advice. Long GP waiting times, misdiagnoses, lack of disclosure by VFRs about recent travel, and the issue of where malaria treatment should be provided were raised as potential barriers to diagnosis and treatment. CONCLUSIONS: Some issues raised by respondents are relevant to all travellers, irrespective of their reason for travel. The challenge for healthcare providers to reduce the burden of imported malaria in VFRs is to provide services of sufficient quality to persuade them to adopt these in preference to those with which they may be familiar in their country of birth. Although no single intervention will significantly lower the burden of imported malaria, addressing the issues raised in this research could make a significant impact.